(Simulated) listener gaze in real‐time spoken interaction. (May 2018) - Frädrich, Laura; Nunnari, Fabrizio; Staudte, Maria; Heloir, Alexis
Abstract: Gaze is an important aspect of social communication. Previous research has concentrated mainly on the role of speaker gaze and listener gaze in isolation, neglecting the effect of the listener's gaze behavior on the speaker's behavior. This paper presents an exploratory eye‐tracking study involving an interactive human‐like agent following participants' gaze. This study demonstrates that a rather simple gaze‐following mechanism convincingly simulates active listening behavior engaging the speaker. The study also highlights how speakers rely on their interlocutors' gaze when establishing common references. Abstract : (Simulated) listener gaze in real‐time spoken interaction Laura Fradrich *Fabrizio Nunnari *Maria Staudte *Alexis Heloir *This paper presents an exploratory eye tracking‐study involving an interactive human‐like agent following participants' gaze. This study demonstrates that a rather simple gaze‐following mechanism convincingly simulates active listening behaviour engaging the speaker. The study also highlights how speakers rely on their interlocutors' gaze when establishing common references.